2016
DOI: 10.1614/ws-d-15-00114.1
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Impact on Weed Dynamics in an Organic Dry Bean System

Abstract: Weed suppression is one possible benefit of including cover crops in crop rotations. The late spring planting date of dry beans allows for more growth of cover crops in the spring. We assessed the influence of cover crops on weed dynamics in organic dry beans and weed seed persistence. Medium red clover, oilseed radish, and cereal rye were planted the year before dry beans; a no-cover-crop control was also included. After cover-crop incorporation, common lambsquarters, giant foxtail, and velvetleaf seeds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 73 publications
5
12
0
Order By: Relevance
“…Residue biomass in other cover crop treatments ranged from 438 kg ha −1 for winter-killed radish to 9,003 kg ha −1 for late-killed cereal rye (Table 3). Cover crop biomass levels were comparable with results reported in previous research in the upper Midwest (Davis 2010; Hill et al 2016).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Residue biomass in other cover crop treatments ranged from 438 kg ha −1 for winter-killed radish to 9,003 kg ha −1 for late-killed cereal rye (Table 3). Cover crop biomass levels were comparable with results reported in previous research in the upper Midwest (Davis 2010; Hill et al 2016).…”
Section: Resultssupporting
confidence: 90%
“…Soil nitrogen also could affect weed density results. Decomposing cereal rye residues typically reduce soil nitrogen availability, which suppresses weed emergence (Hill et al 2016). However, radish residues, which may also reduce soil nitrogen availability, have shown mixed effects on weed emergence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He did note, however, that germination responses of all species in the genus are highly variable and change with environmental conditions. In a study similar to ours, Hill et al (2016) found that incorporated red clover had no effect on persistence of S. faberi . We conclude that incorporated legume cover crops are likely to have a weak or inconsistent effect on the persistence of S. faberi .…”
Section: Resultssupporting
confidence: 82%
“…Conservation agriculture systems hold promise for combining improvements in soil quality and weed management without becoming overly reliant on herbicides. Cover cropping, as one of the main pillars of conservation agriculture, provides numerous well‐known ecological and agronomic benefits in crop production systems, notably water conservation, improving soil and water quality, enhancing soil productivity and weed suppression (Mirsky et al ., , ; Wells et al ., ; Hill et al ., ). Cereal rye has specific traits that make it an ideal fall(autumn)‐planted cover crop in many agronomic systems, such as possessing appropriate agronomic traits as a cover crop, soil and water quality improvements and suppressing weeds (Barberi & Mazzoncini, ; Smith et al ., ; Teasdale et al ., ; Mirsky et al ., ).…”
Section: Introductionmentioning
confidence: 97%